Serum hepatitis B core‐related antigen as a treatment predictor of pegylated interferon in patients with HBeAg‐positive chronic hepatitis B. (5th January 2016) - Chuaypen, Natthaya; Posuwan, Nawarat; Payungporn, Sunchai; Tanaka, Yasuhito; Shinkai, Noboru; Poovorawan, Yong; Tangkijvanich, Pisit
Abstract: Background & Aims: The role of quantitative serum hepatitis B core‐related antigen (HBcrAg) in patients with chronic hepatitis B (CHB) receiving pegylated interferon (PEG‐IFN) is unclear. This study was aimed at comparing its usefulness with quantitative HBsAg in patients with HBeAg‐positive CHB receiving PEG‐IFN therapy. Methods: A total 46 patients treated with PEG‐IFN for 48 weeks were retrospectively analysed. Intrahepatic covalently closed circular DNA (cccDNA) from paired liver biopsies and serial serum HBsAg and HBcrAg during therapy were assessed. Results: Virological response (VR), defined as HBeAg clearance and HBV DNA <2000 IU/ml at 24 weeks post treatment, was achieved in 15 (32.6%) patients. Responders had significantly higher cccDNA decline from baseline compared with non‐responders. Baseline HBsAg and HBcrAg were correlated with cccDNA ( r  = 0.424, P  =   0.020 and r  = 0.564, P  =   0.001, respectively), and changes in the corresponding markers during therapy were correlated with cccDNA reduction ( r  = 0.579, P  =   0.001 and r  = 0.503, P  =   0.005, respectively). Responders showed more rapid decline of both markers during therapy compared with non‐responders. In multivariate analysis, serum HBcrAg at week 12 was identified as a predictor of VR. The optimal cut‐off value for HBcrAg (log10 8.0 U/ml) provided negative predictive value (NPV) of achieving VR at weeks 12 and 24 of 94.4 and 100%, respectively, while using HBsAg > 20 000 IU/ml provided NPV of 80 and 100% respectively. Conclusions: The convenient quantitative HBcrAg represented a reliable marker of intrahepatic cccDNA. Monitoring HBcrAg levels during PEG‐IFN therapy may help identify patients with a very low probability of response comparable to, if not better than, quantitative HBsAg.